2020
DOI: 10.1039/c9cp06726d
|View full text |Cite
|
Sign up to set email alerts
|

Operando XANES from first-principles and its application to iridium oxide

Abstract: Efficient electro-catalytic water-splitting technologies require suitable catalysts for the oxygen evolution reaction (OER). The development of novel catalysts could benefit from the achievement of a complete understanding of the reaction mechanism on iridium oxide (IrO 2 ), an active catalyst material that is, however, too scarce for large-scale applications. Considerable insight has already been provided by operando X-ray absorption near-edge structure (XANES) experiments, which paved the way towards an atom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…This redox change at higher potentials is important to note since mostly an increase of the Ir oxidation state at applied OER potentials was observed, which are also highly oxidizing conditions. [30][31][32][33]49 However, the applied potentials used here are also higher than in these previous studies.…”
Section: ■ Resultsmentioning
confidence: 80%
“…This redox change at higher potentials is important to note since mostly an increase of the Ir oxidation state at applied OER potentials was observed, which are also highly oxidizing conditions. [30][31][32][33]49 However, the applied potentials used here are also higher than in these previous studies.…”
Section: ■ Resultsmentioning
confidence: 80%
“…We first observe R-IrO 2 (110) to be more stable than R-IrO 2 (100) under both synthesis and OER conditions, in agreement with previous studies. 59,60 For α-IrO 2 , the (101) facet is less stable than the (100) facet for all chemical potentials less oxidative than the OER conditions, although this effect is less pronounced when considering surface energies normalized per surface area instead of surface units (Figure S3). This result is consistent with the larger number of Ir-O bonds broken (4 vs. 3 per surface unit) at the surface for the (101) facet compared to that for the (100) facet (Figure S14 and Table S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Four low-index facets ([001], [100], [101], [110]) were considered, the most stable coverages at the reaction condition were determined, and catalytic activities of all unique active sites were evaluated . Although not all facets are equivalently stable because of different surface energies and the relative stability of facets could be affected by the electrode potential, it is much more informative to consider various possible facets instead of focusing only on the most stable one. For example, it was found that an exhaustive search of active sites by modeling multiple facets could rationalize the experimental observations of interesting catalytic properties of Ni–Ga catalysts for CO 2 reduction .…”
Section: Resultsmentioning
confidence: 99%